Nuclear Thermal Hydraulic and Two-Phase Flow - Jun Wang (Frontiers Research Topics, 2018)
Nuclear energy is one of the most important clear energy and contributes more than 10% electric power to human society in the past decades of years. The nuclear thermal hydraulic and two-phase flow is one of the basic branches of nuclear technology and provides structure design and safety analysis to the nuclear power reactors. In the new century, the basic theoretical research of thermal hydraulic and two-phase flow, and innovative design for the next generation nuclear power plants (especially for the small modular reactor and molten salt reactor), along with other nuclear branches, constantly support the development of nuclear technology.